Resisting Paranoid Doctrines and Logic of Violence: A Saidian Literary Humanist Perspective on Selected South Asian Short Fictional Narratives - Khan, Saleem Akhtar; Iqbal, Nasar (Pakistan Languages and Humanities Review, 2023)
This paper studies how the selected South Asian short fictional narratives thematize the humanist dimensions by repudiating the brutal logic of violence perpetuated through paranoid patriotism and insular exclusivism. Situating the critique at the theoretical pivot of Edward Said’s argument for indispensability of the humanist endeavours in the wake of all-pervasive belligerency the world over, as presented in one of his later works Humanism and Democratic Criticism (2004), the study approaches two of the tragic narratives taken from Zaman and Farrukhi’s anthology Fault Lines (2008): Masood Mufti’s “Sleep” and Mohan Kalpana’s “Traitor”. Both of the selected stories are marked by the strains of “circumstantiality” and “historical contingency” with a focus on portrayal of the instances of ferocity resulting from the spurious sloganeering and predisposition to nationalist prejudice. Through a thorough textual analysis of the primary sources, guided by the theoretical framework, representations of the peculiar exploitative pattern of violence and unwarranted deeds of the perpetrators have been discussed. Thus, the critique shows that the selected South Asian short stories deprecatingly represent exclusivist nationalism and the consequent violence to proffer a humanist vision and plead for co-existence.